What brings adults with Down syndrome to the hospital? A retrospective review of a Spanish cohort between 1997 and 2014. Issue 1 (29th October 2022) - Aparicio, Paloma; Barba, Raquel; Moldenhauer, Fernando; Suárez, Carmen; Real de Asúa, Diego
Abstract: Objectives: To describe the clinical and epidemiological characteristics of adult patients with Down syndrome admitted to Spanish hospitals between 1997 and 2014. Secondary goals were to study trend changes over time, and to analyse differences between patients admitted to medical and surgical departments. Patients and Methods: Retrospective observational study on data collected from the Minimum Basic Dataset (MBDS, Conjunto Mínimo Básico de Datos [CMBD]) of admissions of adults with Down syndrome to hospitals belonging to the Spanish National Health System from 1 January 1997 through 31 December 2014. We analysed epidemiological and clinical variables. Results: We analysed 28, 716 admissions of 16, 874 adult patients with Down syndrome. Men accounted for 58.2% of the sample, and the mean age on admission was 41 ± 13 years, with an 11‐year increase in mean age during the study period. Admissions among persons with Down syndrome increased by 5% during the study period, with a noticeable rise in admissions of older adults and to medical departments. Almost one‐third of patients (31.8%) were admitted more than once. Age‐adjusted mortality was 15.7%. The most common comorbid conditions were chronic obstructive pulmonary disease (25%), hypothyroidism (18.6%), and epilepsy (14.3%). The departments with the highest numbers of admissions were internal medicine (26.3%), pulmonary medicine (6.9%), and general surgery (5.25%). Conclusion: Hospital admissions among Spanish adults with Down syndrome have increased in recent decades, especially in older patients. We identified substantial differences between patients admitted to medical and surgical departments.